ANALISA PENERAPAN INVENTARISASI BARANG MASUK & KELUAR DALAM MEMINIMALISIR TERJADINYA KESALAHAN SELAMA STOCK OPNAME DI TOKO VIOLETA STORE MATARAM MALL TAHUN 2024 - Safitri, Juliana; Slamet Mardiyanto Rahayu; Fathurrahman; Muhammad Habibullah Aminy; Lale Ajeng Khalifatun Wardani; Muhammad Aditya Rachman (Nusadaya Journal of Multidiciplinary Studies, 2024)
Inventory activities are an essential process in company asset management, encompassing the systematic collection and recording of data on goods. One of the main activities in inventory management is stock opname, which involves physical inspection of goods to match administrative records with the actual condition of the inventory. This study aims to analyze how the recording of incoming and outgoing goods can minimize errors during the stock opname process at Violeta Store, Mataram Mall. The study uses a descriptive method with a qualitative approach through observation, documentation, and interviews conducted over one week. The results show that the inventory system is still done manually, although it follows the company's Standard Operating Procedures (SOP) consistently. However, human error frequently occurs due to a lack of employee accuracy, and the stock opname process is not always performed on a consistent schedule. Inaccuracies between stock opname results and recorded data are still found. Therefore, the implementation of a digital system, such as barcode usage, is highly recommended to improve accuracy and efficiency in managing inventory data